Effect Of Manufacturing Processes On The Methanol Content For Some Industrial Fermentations - رامز محمد; شيم سليمان; يحيى اسماعيل (Latakia University Journal -Biological Sciences Series, 2022)
Methanol is one of the most important dangerous toxins its formed in the fermentation medium, as a result of the enzymatic hydrolysis of pectin by the enzyme pectin methylesterase (PME), especially in uncontrolled fermentation industries. This research aims to determine the effect of storage cooled time for grapes on (0±1) ℃ and the nature of the mash as well as the initial microbial load on the methanol concentration in the fermented mash. Where 33 samples were analyzed using the chromaticity method (as a reference method), which is based on measurement in the visible ray field with a wavelength (575 nm) using a spectrophotometer. Where coold storage of the fruits led to the formation of methanol at a rate of 75.95 mg/100 ml after 90 days of storage, and severe mashing of the fruits led to an increase in the methanol concentration of 25.6% compared to traditional mashing, this is in the fermentation products, and the methanol concentration was also affected by the initial load of yeasts and fungi. The concentration increased with the increase in the general census.